Construction and properties of the silk fibroin and polypropylene composite biological mesh for abdominal incisional hernia repair - Luan, Fengming; Cao, Wangbei; Cao, Chunhui; Li, Baizhou; Shi, Xiaoyu; Gao, Changyou (Frontiers in Bioengineering and Biotechnology, 2022)
Background: A new composite biological mesh named SFP was prepared by combining silk fibroin with polypropylene mesh in this study. The mechanism and clinical application value of SFP composite mesh were explored. Methods: The fibrous membrane was prepared by electrospinning of silk fibroin. The silk fibrous membrane was adhered to polypropylene mesh by fibrin hydrogel to make a new composited mesh. The characterizations were verified by structural analysis and in vitro cell experiment. Forty Sprague-Dawle rats were randomly divided into two groups, and 20 rats in each group were implanted with SFP mesh and pure polypropylene mesh, respectively. The rats were sacrificed in batches at 3rd, 7th, 14th and 90th day after surgery. The adhesion degree and adhesion area on the mesh surface were compared, and the histopathological examination was carried out. Results: In vitro cell function experiments confirmed that SFP mesh had good cell viability. The control group had different degrees of adhesion at 3rd, 7th, 14th and 90th day after surgery. However, there was almost no intraperitoneal adhesions at 3rd and 7th day after surgery, and some rats only had mild adhesions at 14th and 90th day after surgery in the SFP group. There were statistically significant differences in postoperative intraperitoneal adhesion area and adhesion degree between the two groups (p< 0.05). Histopathological examination confirmed that the mesenchymal cells were well arranged and continuous, and there were more new capillaries and adipocytes proliferation under the mesenchymal cells in the SFP group. Conclusions: SFP mesh shows good biocompatibility and biofunction in vitro and in vivo. It can promote the growth of peritoneal mesenchymal cells. The formation of new mesenchymal cell layer can effectively reduce the extent and scope of adhesion between mesh and abdominal organs. The SFP mesh will have a good application prospect in the field of abdominal wall hernia repair.